Pengembangan Perbatasan Indonesia Menggunakan Data Wisatawan Mancanegara - Agita Arrasy Asthu (Kelompok Peneliti Muda Universitas Negeri Jakarta, 2021)
In the proportion of the development, making it more difficult for the border regions to pursue progress. This study uses Growth–share matrix method to rank which boundaries are the development priorities. The data variables used are those of foreign tourist visits (Mobile Positioning Data) and growth. The study was conducted in 18 regencies that were the subject to study. From these data, the authors divided into four development categories, namely high market share in low growing markets, high market growth but low market share, high market share and high market growth, and low market share and low growth rates. To eliminate the imbalance, tourism approach can be an alternative.